Etiological structure of bacteriosis of animals in the Dnipropetrovsk region for 2014–2016 - Glebenyuk, Volodymyr; Glebenyuk, V. V.; Глебенюк, Володимир Володимирович; Borovik, Irina; Боровик, Ірина Володимирівна; Kuchuk, Tetjana; Кучук, Тетяна Валеріївна; Litvinenko, Oleksandr (Львівський національний університет ветеринарної медицини та біотехнологій ім. С. З. Ґжицького, 2018)
The epizootic situation with regard to some infectious diseases in the Dnipropetrovsk region remains as complicated and strained. Timely and accurate diagnosis determines the effectiveness of the realized preventive measures of infectious diseases and establishes the peculiarities and changes of the epizootic situation in certain areas. The laboratory examinations, including the bacteriological method, have the crucial importance for the correct assessment of prevention and antiepizootic measures. Objective of this review: was to determine the etiological structure of infectious diseases in the Dnipropetrovsk region for 2014–2016, based on the results of bacteriological examinations. As the material for the examinations were the data of the veterinary reports of the State district veterinary medicine laboratories of the Dnipropetrovsk region and the results of our own examinations conducted on the basis of the Dnipropetrovsk Regional State Laboratory of the Veterinary Medicine (DRSLVM). As of 2014 year, in the Dnipropetrovsk region, the live-stock capita in all categories of farms was: horned cattle – 130,527, small cattle – 44,739, pigs – 520,801, horses – 1,781, poultries – 15,342,087, including chickens – 14,816,157, waterfowl – 525,930. During 2014–2016 by means of laboratories of veterinary medicine in the Dnipropetrovsk region have been conducted 18,474 examinations on the infectious diseases of the animals. 142 positive results were received in total. According to the results of the bacteriological examinations in the Dnipropetrovsk region, for the years 2014–2016 were registered diplococcosis, malignant edema, pasteurellosis, colibacteriosis, salmonellosis, pullorosis, staphylococcosis, streptococcosis and swine erysipelas, poultry pseudomonosis, aeromonosis of fish, parafoul brood (caused by Bacillus paraalvei) and proteose of bees. 4,472 examinations were conducted on colibacteriosis and 78 positive results were obtained. 21 cultures were obtained from the pigs, from poultries – 44 cultures, from embryos – 6 cultures, from small cattle – 3 cultures, from fur animals – 2 cultures, from dogs – 2 cultures. Cultures of Escherichia coli, isolated from pigs are represented by the serological variants: O139, O26, O9, O78, O1, O8 and atypical variants, and from poultries – O115, O119, O78, O15, O86, K88 AB and atypical variants. For salmonella, 7,578 examinations were conducted and 16 positive results were obtained. Among the diseases of bees, laboratory tests have been recorded parafoul brood and proteose of bees. Conclusion: сausative agents of 13 infectious animal diseases have been identified in the Dnipropetrovsk region by means of bacteriological investigations. Most commonly isolated pathogens of intestinal infections (colibacteriosis and salmonellosis). Епізоотична ситуація щодо деяких інфекційних хвороб на Дніпропетровщині залишається складною і напруженою. Своєчасна і точна діагностика визначає ефективність реалізованих заходів профілактики інфекційних хвороб та встановлює особливості і зміни епізоотичної ситуації на певних територіях. Лабораторні дослідження, в тому числі бактеріологічний метод, мають вирішальне значення для правильної оцінки профілактичних і протиепізоотичних заходів. Метою нашої роботи було визначити за результатами бактеріологічних досліджень етіологічну структуру інфекційних хвороб у Дніпропетровській області за 2014–2016 роки. Матеріалом для досліджень були дані ветеринарної звітності державних районних лабораторій ветеринарної медицини Дніпропетровської області та результати власних досліджень, проведені на базі Дніпропетровської регіональної державної лабораторії ветеринарної медицини (ДРДЛВМ). Станом на 2014 рік у Дніпропетровській області поголів’я тварин по всіх категоріях господарств становило: великої рогатої худоби – 130527, дрібної рогатої худоби – 44739, свиней – 520801, коней – 1781, птахів – 15342087, у тому числі курей – 14816157, водоплавної – 525930. Упродовж 2014–2016 рр. лабораторіями ветеринарної медицини у Дніпропетровській області було проведено 18474 дослідження на інфекційні захворювання тварин. Всього було отримано 142 позитивні результати. За результатами бактеріологічних досліджень у Дніпропетровській області за 2014–2016 рр. було зареєстровано диплококоз, злоякісний набряк, пастерельоз, колібактеріоз, сальмонельоз, пулороз, стафілококоз, стрептококоз та бешиху свиней, псевдомоноз птиці, аеромоноз риб, парагнилець та протез бджіл. На колібактеріоз проведено 4472 дослідження і одержано 78 позитивних результатів. Від свиней отримано 21 культуру, від птиці – 44 культури, від ембріонів – 6 культур, від дрібної рогатої худоби – 3 культури, від хутрових звірів – 2 культури, від собак – 2 культури. Культури Escherichia coli, виділені від свиней представлені серологічними варіантами: O139, O26, О9, О78, О1, О8 та нетипованими, а від птиці – O115, O119,О78, О15, О86, К88 АБ та нетипованими. На сальмонельоз проведено 7578 досліджень і отримано 16 позитивних результатів. Серед хвороб бджіл лабораторними дослідженнями було зареєстровано парагнилець та протеоз бджіл. Висновки: у Дніпропетровській області бактеріологічними дослідженнями виділено збудників 13 інфекційних хвороб тварин. Найбільш часто виділялися збудники кишкових інфекцій (колібактеріозу та сальмонельозу).
Етіологічна структура бактеріозів тварин у Дніпропетровській області за 2014–2016 роки
Keywords: Dnipropetrovsk region; Дніпропетровська область; bacteriosis; бактеріози; animals; тварини; colibacteriosis; колібактеріоз; salmonellosis; сальмонельоз; bacteriological examinations; бактеріологічні дослідження